Comparative performance of Giriraja chicken reared on different feeding regimes for economic production in Nepal - Neupane, D; Bhandari, BB; Poudel, S; Shrestha, S; Sapkota, S (Bangladesh Journal of Animal Science, 2017)
The experiment was conducted to study the comparative performance of Gririaja birds reared on different feeding regime in Nepal. A total of 384 Giriraja birds of aged 40 weeks were assigned to four treatment groups in four replications with 24 birds (20 female and 4 male) per replication over a period of 180 days. The birds of control group were provided with 130g of feed in confinement. In group 1, 10% feed was replaced by green seasonal forage mainly oat and birds were kept on scavenging, while in group 2, 10 % feed was replaced by similar forage but the birds were in confinement. However, in group 3, birds were provided 10 % less feed on scavenging without forage supplementation. The result showed that the feed consumption required for dozen of egg production was lower (P<0.01) at 2610 g/bird in group 1 and higher (3114 g/bird) in control group. The birds kept in control and in group 1 was found significantly (P<0.05) superior in egg production as compared with the second and third treatment groups (15.05 and 16.15 vs. 15.55 and 14.31 in number, respectively). There was no significant difference on egg weight between the groups. Feed cost for dozen of egg production was recorded 1.17 and more gross returns from sale of eggs ( 0.27) was observed in treatment group 1 but less return ( 0.04) was obtained from control group. The result showed that rearing of Gririaja birds with forage supplementation having the facilities of outdoor range is a good profitable venture, considering the minimum feed consumption and feed cost with maximum egg production. Bang. J. Anim. Sci. 2017. 46 (2): 134-139